Effect of Massachusetts health insurance reform on mammography use and breast cancer stage at diagnosis. Issue 2 (25th July 2012) - Keating, Nancy L.; Kouri, Elena M.; He, Yulei; West, Dee W.; Winer, Eric P.
Abstract BACKGROUND: Massachusetts law requires all residents to maintain a minimum level of health insurance, and rates of uninsurance in that state decreased from 6.4% in 2006 to 1.9% in 2010. The authors of this report assessed whether health insurance expansion was associated with use of mammography and earlier stage at breast cancer diagnosis. METHODS: By using a prereform/postreform design with a concurrent control (California), mammography rates in the last year were assessed using the Behavioral Risk Factor Surveillance System survey and the diagnosis of stage I (vs II/III/IV) breast cancers based on cancer registry data among women ages 41 to 64. Propensity score analyses were used to compare California women who were most similar to women in Massachusetts with Massachusetts women. RESULTS: Among propensity‐weighted cohorts, adjusted mammography rates in Massachusetts were 69.2% in 2006, 69.5% in 2008, and 69.0% in 2010. In California, the rates were 59% in 2006, 60.3% in 2008, and 56.2% in 2010 (P = .89 for interaction by state for 2010 vs 2006). Among propensity‐weighted cohorts, adjusted rates of diagnosis with stage I cancers were 52.2% in 2006, 53.5% in 2007, and 52.4% in 2008 in Massachusetts versus 46.4% in 2006, 46.3% in 2007, and 45.7% in 2008 in California (P = .58 for interaction by state for 2010 vs 2006). CONCLUSIONS: Health insurance reform in Massachusetts was not associated with increased rates of mammography or earlier stage at diagnosis compared with California, possibly because of insurance and mammography rates that already were high. Additional research is needed to assess the impact of insurance expansions in other populations, especially those with higher uninsurance rates. Cancer 2013. © 2012 American Cancer Society.